The "Well-Being" and "Ill-Being" of Online Impulsive and Compulsive Buying on Life Satisfaction: The Role of Self-Esteem and Harmony in Life. (March 2022) - Olsen, Svein Ottar; Khoi, Nguyen Huu; Tuu, Ho Huy
The antecedents and implications of shopping are relevant to impulsive and compulsive buying behaviour, because both tendencies can be harmful to an individual's well-being, ill-being, and for society as regards overconsumption and sustainability. Most studies investigating either impulsive or compulsive buying have used different definitions and operationalisations of the two constructs. It is unclear whether impulsive buying and compulsive buying are both parts of shopping ill-being. This study defines and measures impulsive buying tendency (IBT) and compulsive buying tendency (CBT) in terms of distinctive core features: impulse versus urge or addiction. It compares their antecedents and consequences in one integrated empirical study, with self-esteem (SE) an antecedent, and satisfaction with life (SWL) a consequence of these two shopping tendencies. To our knowledge it is also the first study to investigate how harmony in life (HIL) is associated with the relationship between SE and IBT/CBT. A survey of 384 consumers indicates that online IBT and CBT differ from a bottom-up consumer well-being perspective. IBT contributes to life satisfaction, but CBT does not. Positive and negative SE have opposite effects on online IBT and CBT, confirming that both can act as self-regulation mechanisms. HIL moderates the relationship between SE and IBT/CBT.